Are there Public Effects of Religious Education?: Assessing the Contribution of Religious Education to the Acceptance of Cultural Diversity, Reticence toward Populism, and Generalized Social Trust among Young People in Germany - Roleder, Felix (Journal of empirical theology, 2025)
This quantitative study examines the effects of religious education, in conjunction with other religious and non-religious factors, on the civic attitudes of Christians under the age of 30 in Germany. The multivariate analyses are based on a recent population representative sample (6th Church Membership Survey). The results provide modest evidence of a limited direct and indirect contribution of religious education to civic attitudes. In addition to a direct reduction in populist attitudes, school religious education is somewhat associated with acceptance of cultural diversity and immigration, thereby also indirectly decreasing the appeal of populism. However, the ambivalent role of young Christians’ religiosity is evident in relation to traditionalism and religious exclusivism, which are associated with a preference for cultural homogeneity and, consequently, an affinity with populism. These findings contribute to the understanding of the current crisis of the acceptance of democracy and underline the public dimension of religious education.